Employment restructuring in the health service : efficiency initiatives, working patterns and workforce composition - Pulkingham, Jane [Verfasser] (My University, 1992)
"The evidence which has accumulated regarding the impact of contracting-out and the implemantation of measures designed to increase 'efficiency' in NHS domestic ancillary services suggests that the circumstances of the jobs concerned have sharply deteriorated. But what are the repercussions of this process, in which employment opportunities have been radically restructuredd, on the profile of the workforce itself? Have there been any significant changes in the workforce composition as a result of the changes in working conditions and employment opportunities? The research presented in this paper suggests that with the restructuring of domestic acillary employment, in particular, the increased reliance on part-time work, the profile of the workforce has changed significantly." (author's abstract) ((en)) Der Beitrag geht der Frage nach, wie sich die Restrukturierung des britischen Gesundheitswesens auf die Beschäftigtenstruktur und die Arbeitsbedingungen ausgewirkt hat. Im Mittelpunkt stehen dabei die Bemühungen um eine Effizienzsteigerung der Versorgungsdienste in Krankenhäusern. (IAB)
Umstrukturierung der Beschäftigung im Gesundheitswesen - Bemühungen um Effizienzsteigerung, Arbeitsbedingungen und Beschäftigtenstruktur
Keywords: G 1.2.2.2 Soziale Sicherungssysteme; G 2.1.1 Ökonomie / Märkte; S 4.3.3 Effizienz & Effektivität des Berufsbildungswesens; G 2.3.1 Arbeitsteilung & -organisation; G 1.2.1 Grund- & Strukturdaten des Arbeitsmarktes; S 5 Organisationsentwicklung; Gesundheitswesen; Privatisierung; Arbeitsbedingungen; Reinigungsberuf; Effizienz; Arbeitsintensität; Berufsproblem; Beschäftigtenstruktur; Quantitative Angaben